2005
DOI: 10.1136/bmj.38404.650208.ae
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of signed consent for the collection of patient identifiable information for a national paediatric clinical audit database

Abstract: ConclusionQuetiapine and rivastigmine seemed of no benefit in patients with dementia and agitation in institutional care, and quetiapine was associated with greater cognitive decline than placebo. Our results suggest that quetiapine should not be used in people with dementia and highlight concerns regarding the long term use of antipsychotics in these patients.We thank the Alzheimer's Research Trust for their support in our programme of work to evaluate the impact of antipsychotics on cognition; Alistair Burns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Consent rates for children in the surveys identified ranged from 43% (McKinney et al 2005) to 92% (Tate et al 2006). Generally, minority groups provided lower consent rates (McKinney et al 2005;Tate et al 2006), with some evidence that higher socioeconomic status related to higher rates of consent (Klassen et al 2005;Tate et al 2006).…”
Section: Lightfoot and Dibben 2013)mentioning
confidence: 99%
See 2 more Smart Citations
“…Consent rates for children in the surveys identified ranged from 43% (McKinney et al 2005) to 92% (Tate et al 2006). Generally, minority groups provided lower consent rates (McKinney et al 2005;Tate et al 2006), with some evidence that higher socioeconomic status related to higher rates of consent (Klassen et al 2005;Tate et al 2006).…”
Section: Lightfoot and Dibben 2013)mentioning
confidence: 99%
“…McKinney et al (2005) sought consent from parents who had children admitted into a paediatric intensive care unit. Tate, Calderwood, Dezateaux & Joshi (2006) asked for birth register and maternity data from a cross-section of mothers of new-borns, but as a single request.…”
Section: Lightfoot and Dibben 2013)mentioning
confidence: 99%
See 1 more Smart Citation
“…When the choice to consent is dependent on characteristics pertaining to the individual or context, the selection of participants for the study is consequently non-random, which introduces the possibility of bias in estimations of associations within the sample (Groenwold et al, 2013;Hernan et al, 2004) It has previously been demonstrated that individuals who consent to medical research participation may be different in several ways from those who decline participation, but consistent patterns are lacking (Kho et al, 2009). For example, several studies have shown that males were more likely to consent (Damery et al, 2011;Knies et al, 2012; Twins' Consent to Research Using Health Records Matsui et al, 2005;Schwartz et al, 2005;Woolf et al, 2000), whereas others have not demonstrated any sex difference in consent rates (Al-Shahi et al, 2005;Baker et al, 2000;Beebe et al, 2011;Buckley et al, 2007;Huang et al, 2007;Klassen et al, 2005;McKinney et al, 2005) and some have seen a higher likelihood of consent among females (Dunn et al, 2004;Kho et al, 2009). The age of the potential study participants may play a part in the choice to consent.…”
mentioning
confidence: 99%
“…In an increasing number of examples, such refusal has resulted in decreased participation, selection bias (Table 2), incomplete research and dismantled disease registries. 1,[6][7][8][9][10][11][12] Fortunately, there are not many published examples from Canada; however, we are still in the relative early days following privacy legislation. Until this legislation is tested and precedents are set, the potential for further detrimental effects on observational research remains.…”
Section: Medicine and Societymentioning
confidence: 99%